A century on from The Biology of Dragonflies by Tillyard 1917: what have we learned since then?. Issue 2 (30th December 2016) - Khelifa, Rassim; Theischinger, Gunther; Endersby, Ian
Abstract: The field of odonatology has developed considerably during the past century. Three figures, namely E. Selys‐Longchamps, R.J. Tillyard and P.S. Corbet, have undisputedly founded our current knowledge of odonatology and contributed massively to the understanding of systematics, biology, ecology and behaviour of odonates. The year 2017 will mark the 100th anniversary of Tillyard's The Biology of Dragonflies . We review the book and the author's life and contributions to Australian odonatology. We present an updated history of odonatology and highlight prominent advances in the field. The influence of the book on non‐scientists is described. Future research in odonatology on aspects that have not been studied and others that need further investigations are discussed.